Green roof infrastructure outperforms grey technology in flood mitigation in São Paulo’s urbanized region - Ferreira, Mauricio Jonas; da Rocha, Humberto Ribeiro (Frontiers in Built Environment, 2023)
São Paulo City, Brazil, a densely urbanized area in a tropical climate region, is facing increasing challenges from flooding. However, a promising solution has emerged in the form of Nature-Based Solutions (NBS) infrastructure, surpassing traditional grey technology in flood mitigation. This article examines the effectiveness of green roofs in reducing flood risks and highlights their superiority over conventional approaches. We analyzed the direct impacts of surface permeabilization in public areas (sidewalks, streets, and squares) and private areas (urban lots, subdivisions) on runoff volume and peak flow in the Aricanduva River basin in São Paulo city. We used a thoroughly validated hydrological model to compare the interference in the land use of the watershed between a green infrastructure type called Green Roof (GR) and a gray technology called Permeable Pavement (PP), in terms of hydrological efficiency in mitigating floods. The flow and water level simulations for varying areas with GR or PP covered a wide range, allowing for situations above or below the canal overflow level, which provided a good distinction of the impact of boundary conditions. Overall, we observed a positive hydrological response, with a reduction in peak flow and runoff volume proportional to the increase in permeable area, and consequently, proportional to the increase in GR or PP surface within the contributing area. As the main contribution, the hydrological performance calculated with the variation of GR was remarkably superior to the variation of PP in terms of requiring a smaller coverage area with interference to prevent overflow or achieve equivalent efficiency. It is worth noting that the substitution of approximately 24% of the gray roof area with GR prevented canal overflow, which is notably lower than the required substitution of approximately 40% for PP interference. We reinforce the relevance of green roofs as an option to mitigate intense hydrological effects in urban areas and, more importantly, paves the way for other NBS with the same hydrological principles and environmental co-benefits to work individually or in combination.